Effect of the Conditions of Transfer on the Structure and Optical Properties of Langmuir Graphene Oxide Films during Deposition on a Substrate - Seliverstova, E.V.; Ibrayev, N.Kh.; Dzhanabekova, R.Kh. (Pleiades Publishing, 2017)
The effect the solvent and transfer pressure of graphene oxide (SLGO) Langmuir–Blodgett films on the physicochemical properties of monolayers, and on their structural and optical properties, is studied. Examination of the physicochemical properties of SLGO monolayers on subphase surfaces that are formed from SLGO dispersions in different organic solvents reveals that monolayer behavior is virtually independent of the solvent. Electron microscope and optical studies show that the monolayers formed from SLGO disper-sions in DMF and acetone have the highest transfer coefficients. It is concluded that the structural heteroge-neity of the surfaces of graphene oxide films results from simultaneous effect of electrostatic interactions between graphene oxide particles and Van der Waals interactions with the solvation shell of the particles. Studies focusing on the effect the pressure of transferring a graphene oxide monolayer onto the surface of a solid substrate has on structural features of LB films show that films produced at low surface pressures have more homogeneous structures.
Keywords: Langmuir–Blodgett films; graphene oxide; structure; optical properties